OPTIMISME DAN HARDINESS PADA DOKTER MUDA DI RUMAH SAKIT UMUM DAERAH ZAINOEL ABIDIN (RSUDZA) BANDA ACEH - Intan Dewi Kumala; Salma M Nasir (State Islamic University (UIN) Ar-Raniry, 2019)
Medical students have two stages of education, as students at universities and young doctors in hospitals. The severity of the young doctor's job demands optimism and hardiness to be able to handle various challenges when carrying out the profession stage that commonly known as co-assistant (Co-Ass) doctor in the hospital. This study aims to examine the relationship between optimism and hardiness in Young Doctors at Banda Aceh Regional Hospital. The sampling technique used in this study is proportionate stratified random sampling with total sample were 198 Young Doctors. The measuring instrument used in this study consisted of two psychological scales, the optimism scale and the hardiness scale. The results of data analysis using the Spearman correlation technique showed a correlation coefficient (r) of 0.664 with a value of p = 0,000 (p <0.05). The hypothesis is accepted so that it can be concluded that there is a positive and significant relationship between optimism and hardiness in young doctors who carry out the professional stage at Banda Aceh Regional Hospital (RSUDZA).